Joint Placement and Communication Optimization of UAV Base Stations in Aerial GPS Denied Environments with Supplementary Node Assistance - Yang, Jimin; Lee, Jongkwan; Lim, Jaesung (International Conference on ICT Convergence, 2024)
There has been an increase in the studies on in-tegrated sensing and communication (ISAC) technology within unmanned aerial vehicles (UAV s), normally relying on global positioning system (GPS) service for accurate positioning. How-ever, the UAV's vulnerability to GPS jamming poses a potential inaccuracy for ISAC systems. Thus, we propose a joint placement and communication model in aerial GPS-denied environment which uses unaffected user equipments (UEs) on ground as reference anchor nodes and supplementary UE node to position the UAV to a near optimal location. Simulation is conducted on clustered UE environments and results confirm that our proposed scheme can optimize the communication power and localization performance of UAV-BS under different accuracy constraints.
Keywords: Communication optimization; Communicationtechnology; Global positioning; In-tegrated sensing and communication; Localisation; Optimal deployment; Placement optimization; Positioning system; Sensing technology; User equipments; ISAC; localization; optimal deployment; UAV